Direct Percutaneous Mitral Annuloplasty in Patients With Functional Mitral Regurgitation: When and How - Gasior, Tomasz; Gavazzoni, Mara; Taramasso, Maurizio; Zuber, Michel; Maisano, Francesco (Frontiers in Cardiovascular Medicine, 2019)
Mitral regurgitation (MR) is a frequent valvular disease among patients deemed too high risk for surgery. Echocardiography along with CT is the primary diagnostic tool for MR and offers a comprehensive 3D assessment in patient selection and screening for the optimal treatment method. The direct percutaneous mitral annuloplasty addresses the underlying mechanisms of functional mitral regurgitation with a less invasive, catheter-based approach. The described here devices proved a satisfactory safety profile, provided significant MR reduction in most of the patients, and were associated with a significant improvement of symptoms. Although long term outcome assessment is needed to support these early reports, the percutaneous mitral annuloplasty is likely to set a new standard of treatment in the forthcoming future.